Digital Governance Models in Greater China: A Comparative Analysis of Public Service Delivery in Mainland China, Hong Kong, and Macao - Yao Zhang (Lecture Notes in Education Psychology and Public Media, 2026)
Digital transformation has become a key driver of public sector innovation, encouraging governments to redesign public service delivery through digital governance. Although Mainland China, Hong Kong, and Macao share cultural and historical connections, their distinct institutional contexts and administrative arrangements have resulted in different digital governance models. This study compares digital governance practices across the three regions to examine how institutional conditions influence governance approaches and public service delivery outcomes. A qualitative comparative case study approach is adopted, drawing on policy document analysis and secondary literature to examine governance frameworks, service delivery mechanisms, and citizen-oriented initiatives. The findings reveal that each region demonstrates different strengths in administrative efficiency, digital accessibility, service responsiveness, and citizen engagement, reflecting the influence of institutional arrangements and policy priorities. By identifying both similarities and differences among the three regions, this study contributes to a deeper understanding of digital governance development in Greater China and provides practical implications for policymakers seeking to enhance public service delivery and promote cross-regional policy learning.